IDENTIFICATION OF BARRIERS TO EXCLUSIVE BREASTFEEDING FOR POST SECTIO CAESAREA MOTHERS IN PAYA PASIR VILLAGE, MARELAN DISTRICT - Elfalini Warnelis Sinaga; Ida Yustina; R Kintoko Rochadi; Nurmaini Nurmaini; Fikarwin Zuska (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
Giving support to women's breastfeeding after cesarean sections is important to adjust their attitudes, belief systems, and external environments, as well as help them improve their confidence. Information support provided by health workers is an initial effort to influence the understanding of mothers and families about the benefits of breastfeeding. This was a qualitative with a phenomenological approach that explores the various experiences of post-cesarean mothers in providing exclusive breastfeeding. The analysis used was thematic analysis with the help of the Nvivo 12 Plus software. The results of this study revealed three main themes regarding obstacles to exclusive breastfeeding for post-sectio caesarean mothers. The themes are anxiety, lack of knowledge, physical discomfort, and lack of support. The anxiety of breastfeeding mothers greatly influences their intention to provide exclusive breastfeeding. The first step in encouraging mothers to continue with exclusive breastfeeding is for health professionals to educate more people about it. Physical discomfort for post-sectio caesarean mothers can increase mothers' anxiety about breastfeeding.